IDENTITY CROSSROADS AND IDENTITY POLICIES IN MONTENEGRO ‒ IN THE FACE OF THE CENSUS RESULTS 2023-2024. - Stanković, Vladan (Political Review, 2025)
The results of the population census conducted in Montenegro in December 2023 show several important indicators. First, a clear division into several national communities: Montenegrins, Serbs, Bosniaks, Albanians... Second, the Montenegrin people have retained the status of the majority people in Montenegro. This majority, however, is only relative (only 2 out of 5 residents of Montenegro belong to the Montenegrin nation). Montenegro is officially a multinational community, without a majority of people. Third, the Serbs have retained the position of the second largest national group in Montenegro. There are 4.2% more Serbs than in the previous census in 2011. Every third resident of Montenegro is a Serb by nationality. Fourth, the Bosniaks have increased their population at the expense of Muslims. They now make up 9.2% of the population. Now, a part of Bosniaks, who previously declared themselves as national Montenegrins, have returned to the Bosniak national corps. Fifth, the number of Albanians has remained within the expected limits (around 5%). The census results reveal the following identity intersections: Montenegrins in the majority want Montenegro as a civil community of national Montenegrins, to which all national-ethnic groups in the country should belong. Supporters of this idea see Montenegro in the regional environment of the European Union and NATO. On the other hand, the majority of the Serbian people in Montenegro see the future in closer integration of Montenegro with Serbia and Bosnia and Herzegovina (Republika Srpska). The majority of Serbian political entities in Montenegro do not oppose membership in the European Union, but advocate non-aligned military neutrality, and see Montenegro outside the NATO pact. Finally, there is a third, middle option of residents who declare themselves Montenegrins, but who also preserve part of their Serbian identity: they speak the Serbian language, or at least attend the canonical church – the Serbian Orthodox Church. This population remains committed to the “democratic values” of EU and NATO membership, but wants to achieve closer relations with Serbia and Bosnia and Herzegovina (Republika Srpska). The government of Milojko Spajić, his political movement (PES) in coalition with the Democrats of Montenegro, forms the backbone of this commitment. Montenegro is seen as a community of equal citizens but also of the peoples who live in it: Montenegrin, Serbian, Bosniak, and Albanian. The idea is that all ruling parties, with the opposition political movement URA of Dritan Abazović, build a reference political framework for control and changeability of power. This would avoid the danger of the return of former Montenegrin President Milo Đukanović’s DPS to power. The defense of democratic mechanisms and the defense of multinational stability remain the core values of these political processes.